DALWA SYARI'AH HOTEL COMMUNICATION STRATEGY IN IMPROVING THE QUALITY OF SERVICE TO GUESTS - Mochammad Arkansyah; Mohammad Hamzah; M. Nashoihul Ibad (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Abstract The principle of the shari'ah era is now one of the innovations in the hospitality business. This principle of shari'ah can be used as a characteristic of a hotel, the development of a hotel based on shari'ah has not become a fairly popular business but it is believed that the development of this shari'ah-based hotel will experience a fairly drastic increase due to the current level of awareness of shari'ah. The purpose of this study is to describe how the communication strategy used by Hotel Dalwa Syari'ah in improving the quality of service to its guests and how the forms of communication used by Hotel Dalwa Syari'ah. In addition to answering the problem, this writing uses descriptive methods of analysis. Which is a procedure as research produces descriptive data in the form of written or spoken words from observable people and behaviors. The subject of this study is the relationship of Hotel Dalwa Shari'ah Bangil, Pasuruan. While the object of this research is the Strategy of Communication Hotel Dalwa Syari'ah in building image.